2013
DOI: 10.7454/mst.v17i1.1921
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Reactor Design with Glycerol Separation to Increase Biodiesel Production Yield

Abstract: The study consisted of reactor design used for transesterification process, effect of glycerol separation on transesterification reaction, determination of biodiesel quality, and mass balance analysis. The reactor was designed by integrating circulated pump/stirrer, static mixer, and sprayer that intensify the reaction in the outer tank reactor. The objective was to reduce the use of methanol in excess and to shorten the processing time. The results showed that the reactor that applied the glycerol separation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Namun demikian, minyak jelantah merupakan triester gliserol dari asam lemak jenuh dan tidak jenuh. Hampir semua minyak goreng murni mengandung 98% trigliserida sedangkan 2% merupakan komponen non-trigliserida seperti monogliserida, tokoferol, asam lemak bebas, fosfolipid,digliserida, serta sedikit komponen zat warna [4]. Minyak jelantah dipilih karena mudah didapat dan dapat menekan biaya produksi.…”
Section: Pendahuluanunclassified
“…Namun demikian, minyak jelantah merupakan triester gliserol dari asam lemak jenuh dan tidak jenuh. Hampir semua minyak goreng murni mengandung 98% trigliserida sedangkan 2% merupakan komponen non-trigliserida seperti monogliserida, tokoferol, asam lemak bebas, fosfolipid,digliserida, serta sedikit komponen zat warna [4]. Minyak jelantah dipilih karena mudah didapat dan dapat menekan biaya produksi.…”
Section: Pendahuluanunclassified
“…Ion exhange resins and magnesium silicates are used in the conventional dry washing. It has been reported that glycerol and methanol are not removed completely to EN 14214 standard when dry washing is used [29].…”
Section: Recent Innovations In Biodiesel Productionmentioning
confidence: 99%
“…It is suggested that understanding this process relative to the creative process will give insight into where and when resources should be focused to enhance creative performance and also the resulting 'quality' of the product designed (Howard et al 2008). The designers generally worked in sequence according to these stages, but it was not impossible that they returned to a previous step if there were mistakes (Rahmat et al 2013). The stages of the study are shown in Fig.…”
Section: Digester Designmentioning
confidence: 99%